Hypoglycemic Effect of Hazelnut and its Effect on Some Sex Hormones in Alloxan Induced Diabetic in Female Rats - El-Khamisy, Abeer, E.; Rezq, Amr, A. (Pakistan Journal of Nutrition, 2013)
Hazelnut is the second richest source of monounsaturated fatty acids among nuts and is rich in vitamins E and B6, phytosterols, folate, L-arginine, polyphenols and fiber. The present study aimed to investigate the hypoglycemic effect of hazelnut and its effect on some sex hormones in diabetic female rats. Animals were randomly assigned to five groups of equal number and weight. Group I, kept as a normal control group; Group II, kept as a diabetic control group, Groups III, IV and V, kept as diabetic groups and feeding supplemented diet with 5, 10 and 15% hazelnuts, respectively. Supplemented diet with 10% and 15% of hazelnut significantly lower food intake compare to the positive control group. Body weight gain significantly increased in treated diabetic group compare with the positive control group. Feeding supplemented diet with hazelnut at the three different levels caused significantly lower in concentrations of blood glucose, total lipids, triglycerides, total cholesterol, AST, ALT, blood urea nitrogen, uric acid and creatinine and significantly lower in levels of insulin, thyroid stimulating, follicle-stimulating and luteinizing hormones compared to that of untreated diabetic rats. Histological study showed hypertrophy and hyperplasia in beta-cells of islets of langerhans associated with pyknosis of their nuclei in positive control rats. Slight hypertrophy in islets of langerhans and congestion of pancreatic blood vessel was showed in pancreas sections of treated rats with 5 and 10% of hazelnut, respectively. However, rats treated with 15% of hazelnut showed apparent normal histological structure. Ovary sections of positive control rats showed dilation and congestion of blood vessel as well as interstitial connective tissue proliferation. Interstitial cells hyperplasia and follicles were showed in ovary of treated rats with 5 and 10% of hazelnut, respectively. Primary oocytes were showed in ovary sections of treated rats with 15% of hazelnut. In conclusions, hazelnut can be readily incorporated into healthy diet to its healthy effect benefits in diabetes and its complication.